Secretoneurin-immunoreactivity in nerve terminals apposing identified preganglionic sympathetic neurons in the rat: colocalization with substance P and enkephalin - Klimaschewski, Lars Peter; Benndorf, K.; Kirchmair, R.; Fischer-Colbrie, R.; Heym, Christine (Journal of chemical neuroanatomy, 1995)
Preganglionic sympathetic neurons projecting to the superior cervical ganglion are innervated by nerve fibers containing classical neurotransmitters as well as neuropeptides. In this study we examined the possible participation of a novel peptide, secretoneurin (a cleavage product of secretogranin II), in regulation of sympathetic outflow to head and neck by using a retrograde labelling-technique combined with immunohistochemistry. In addition, the coexistence of secretoneurin with substance P and leu-enkephalin, peptides known to innervate preganglionic neurons, was investigated. The majority of retrogradely labeled neurons were localized in the nucleus intermediolateralis of spinal cord segments T1-T3 (maximum at T2). Nearly all of Fast Blue positive neuronal perikarya were apposed by nerve fibers and terminals exhibiting immunoreactivity to secretoneurin. The main secretoneurin-immunoreactive form found in the upper thoracic segments corresponded to the free peptide secretoneurin as revealed by chromatography and radioimmunoassay. More than half of labeled neurons were surrounded by nerve endings containing in addition substance P or leu-enkephalin which were also, however, less frequently colocalized. Our results suggest that secretoneurin influences the activity of preganglionic sympathetic neurons projecting to the superior cervical ganglion. Regarding their frequent colocalization with substance P and leu-enkephalin, functional interactions of these peptides on preganglionic sympathetic nerve activity have to be considered.